2013
DOI: 10.5194/bg-10-4273-2013
|View full text |Cite
|
Sign up to set email alerts
|

Upper Arctic Ocean water masses harbor distinct communities of heterotrophic flagellates

Abstract: Abstract. The ubiquity of heterotrophic flagellates (HFL) in marine waters has been recognized for several decades, but the phylogenetic diversity of these small (ca. 0.8–20 μm cell diameter), mostly phagotrophic protists in the upper pelagic zone of the ocean is underappreciated. Community composition of microbes, including HFL, is the result of past and current environmental selection, and different taxa may be indicative of food webs that cycle carbon and energy very differently. While all oceanic water col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 88 publications
0
19
0
Order By: Relevance
“…Eukaryotic microbial communities from rDNA have been used to infer water mass history (Hamilton et al, 2008;Monier et al, 2013;Zhang et al, 2014), whereas taxa from rRNA are thought to more closely indicate active representatives of the community (Campbell and Kirchman, 2013;Hunt et al, 2013). Here, we found that for both DNA and RNA sourced samples, the surface communities always clustered together separate from the SCM communities.…”
Section: Interpretation Of Dna and Rna-derived Abundances And Diversitymentioning
confidence: 75%
See 1 more Smart Citation
“…Eukaryotic microbial communities from rDNA have been used to infer water mass history (Hamilton et al, 2008;Monier et al, 2013;Zhang et al, 2014), whereas taxa from rRNA are thought to more closely indicate active representatives of the community (Campbell and Kirchman, 2013;Hunt et al, 2013). Here, we found that for both DNA and RNA sourced samples, the surface communities always clustered together separate from the SCM communities.…”
Section: Interpretation Of Dna and Rna-derived Abundances And Diversitymentioning
confidence: 75%
“…All OTU representative reads were aligned in PyNast (Caporaso et al, 2010a), manually curated in BioEdit v.7.2.5 (Hall, 1999) and used to construct a phylogenetic tree (FastTree; Price et al, 2010). Assignment of taxonomic identity was performed in mothur with a 0.8 confidence threshold against the Northern Reference Database v.1.0 , which follows the Silva taxonomy but includes high-quality longer environmental sequences from the Arctic and North Atlantic (Terrado et al, 2009(Terrado et al, , 2011Charvet et al, 2012;Monier et al, 2013;Dasilva et al, 2014). However, using this database, around 30-45% of the reads were still not classified beyond "Other Dinoflagellates" or "Other Ciliates.…”
Section: Post-sequence Data Processing and Taxonomic Classificationmentioning
confidence: 99%
“…One of the projects focused on sea ice sampled in the Amundsen Gulf region in spring 2008 (17). Sample collection and pyrosequencing are described in associated publications (9,17,19,24,29) and were similar for all data sets. To increase pan-Arctic coverage, additional samples that had been collected during various missions between 2005 and 2011 were also sequenced and analyzed using similar methods; these samples were from the Chukchi Sea, the Canadian Arctic Archipelago (Archipelago), Baffin Bay, Hudson Bay, and the Laptev Sea as detailed below.…”
Section: Methodsmentioning
confidence: 99%
“…However, the consequences for HF taxa are not known, in part because few studies have characterized the diversity and biogeography of different HF (15,16). Although there have been a number of studies using V4 18S rRNA gene amplicon pyrosequencing in the Arctic (9,(17)(18)(19), none were focused on pan-Arctic comparisons. All of these studies have detected an effect of environmental gradients on one or more HF taxa, but the extent to which HF with similar putative ecological roles (e.g., bacterivory) might vary in relative abundance over space and time is not yet understood, and a comprehensive analysis is lacking.…”
mentioning
confidence: 99%
“…The development of molecular techniques, especially high-throughput sequencing (HTS), has made it possible to study the diversity and assemblages of pico-and nanosized eukaryotic plankton as well (19)(20)(21)(22). This has resulted in several diversity surveys of microbial eukaryotes from the Arctic Ocean and the shelf seas (23)(24)(25)(26)(27). Pico-and nanosized planktons are now known to govern major processes in the oceans to a larger degree than previously assumed (6,7,28,29).…”
mentioning
confidence: 99%